Educational predictors of violent recidivism following release from prison: An administrative data study. - Dickson, Hannah; Short, Roxanna; Fazel, Seena; Blackwood, Nigel (International Journal of Population Data Science, 2025)
Objectives One in four individuals convicted of a serious violent offence will re-offend within two years in England and Wales. Although educational factors such as exclusion are associated with violent offending, they are not currently incorporated into risk of re-offending assessments. We will establish which educational factors are associated with violent recidivism to help to inform the development of risk assessment in this area. Methods We will use UK administrative data from the linked Police National Computer and National Pupil Database including the prison discharge and population datasets. We will undertake multilevel Cox proportional hazard regression to examine the association between educational risk factors and violent recidivism following release from prison among individuals born between academic years 1989/1990 -1999/2000. Education factors will include: school type, Special Educational Needs (SEN) provision, SEN type, school suspension or exclusion; Academic attainment at 11, 16 and 18 years, and measures of deprivation. Results This ADR UK funded research fellowship started in October 2024 with data access granted in January 2025. In my talk, I will share findings on whether early education factors can predict later violent recidivism following release from prison after adjusting for prison security level, age, sex, ethnicity and index offence type. Conclusion Findings from this project could: (1) improve violence risk assessment tools’ predictive performance; (2) support critically informed professional judgement and decision making in the Criminal Justice System; and (3) promote the importance of early childhood interventions at a public health level.